Analysis of the Malaysian construction industry professional employee turnover antecedents - Siti Hawa Mohd Kasmuri; Zulhabri Ismail; Rumaizah Mohd Nordin; Norfashiha Hashim (Penerbit Universiti Kebangsaan Malaysia, 2022)
In construction, the successful completion of a project is accomplished through an of efficient project management. All construction-related disciplines working together are responsible for the completion of the project by the stipulated completion date. However, poor professional employees’ retention is a significant issue in the construction industry. The objective of this paper is to identify the determinants of employee turnover in the Malaysian construction industry with a focus on professional employees. This study employed a doctrinal research approach consisting of a qualitative research design. Two databases were used, in which four cases were obtained from the Labour Court and 19 cases were obtained from the Industrial Court. Data has been analysed through application of the thematic analysis concept. Findings in this study indicate three main themes of employee turnover determinants in construction industry namely organisation, personal and external determinant. Inconsistencies of finding were found in current data as compared to previous studies including training and development, compensation, stress, job satisfaction and external determinants. Since the data focuses on Malaysia court cases, it is recommended that in the future data from other countries to be included. It is also proposed that a diverse range of industries should be analysed in future studies to arrive at an in-depth conclusion. Finally, recommendation for future studies to include more occupational groups for more generalised findings.